Length Weight Relationship and Condition Factor of Yellowstripe Scad Selaroides leptolepis in Banda Sea Waters, Morowali - Ahmad Musyali; Indri Afriani Yasin; Talha Dangkua; Dewi Shinta Achmad; Arfan Tilome (International Forum of Researchers and Lecturers, 2026)
Yellowstripe scad (Selaroides leptolepis) is an economically important small pelagic fish that supports coastal livelihoods and local food supply in Morowali, Central Sulawesi. Increasing fishing pressure in Banda Sea waters requires location-specific biological information to guide sustainable management. This study analyzed length-frequency distribution, length-weight relationship, growth pattern, and condition factor of yellowstripe scad landed in Bete-Bete Village, Bahodopi District, Morowali Regency. Sampling was conducted from March to May 2026 using 450 individuals obtained from local fishers, with approximately 150 fish sampled each month. Total length ranged from 138 to 203 mm, and catches were dominated by the 171–190 mm size range, especially the 178–183 mm and 184–190 mm classes. Length-weight relationships showed strong positive associations, with coefficients of determination ranging from 79.88% to 94.79%. Growth was generally isometric across sex and month, except for male fish in March, which showed negative allometric growth. Condition factor values were mostly above 1.0 and generally ranged from approximately 1.0 to 1.4, indicating good physiological condition and sufficient habitat support. The findings indicate that yellowstripe scad in Banda Sea waters around Morowali remain in relatively healthy biological condition. However, precautionary management is still required through minimum catch-size regulation, improved gear selectivity, and routine landing-site monitoring.